1994
DOI: 10.1182/blood.v84.2.616.bloodjournal842616
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of stimulated integrin surface expression in human neutrophils by tyrosine phosphorylation

Abstract: The control of the adhesive properties of human neutrophils is an essential element of their defense function. One level at which this control is exerted involves the upregulation of the surface expression of beta 2-integrins. In this study, we have examined the potential involvement of tyrosine phosphorylation in the latter process. Two inhibitors of tyrosine kinases with differing modes of action, erbstatin and herbimycin A, were found to inhibit the expression of CD11b and CD18 stimulated by chemotactic fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…This high affinity confirmation can be detected using an activation specific antibody, CBRM1/5 [9]. As expected, stimulation with IL-8 led to an increase in Mac-1 affinity, as measured by the binding of CBRM1/5 ( Figure 5A) [22]. Pretreatment with calphostin C had no effect on IL-8-mediated changes in Mac-1 affinity, but pretreatment of neutrophils with chelerythrine chloride (data not shown) or the PKCζ pseudosubstrate prior to stimulation with IL-8 actually increased Mac-1 affinity above and beyond the level attained with IL-8 alone ( Figure 5A).…”
Section: Blocking Pkcζ Increases Mac-1 Affinitysupporting
confidence: 73%
“…This high affinity confirmation can be detected using an activation specific antibody, CBRM1/5 [9]. As expected, stimulation with IL-8 led to an increase in Mac-1 affinity, as measured by the binding of CBRM1/5 ( Figure 5A) [22]. Pretreatment with calphostin C had no effect on IL-8-mediated changes in Mac-1 affinity, but pretreatment of neutrophils with chelerythrine chloride (data not shown) or the PKCζ pseudosubstrate prior to stimulation with IL-8 actually increased Mac-1 affinity above and beyond the level attained with IL-8 alone ( Figure 5A).…”
Section: Blocking Pkcζ Increases Mac-1 Affinitysupporting
confidence: 73%
“…Cycloheximide clearly inhibited this process, suggesting a de novo synthesis of these adhesion molecules, in agreement with our finding that transcription levels of the genes encoding the four integrin chains were enhanced in PMA-treated cells. It has been reported that LTB4, a naturally occurring eicosanoid mediator which is mainly known as a chemoattractant for human neutrophils, will up-regulate neutrophil cell surface b2-integrin expression as well as enhance their adhesiveness to endothelial cells [29,30,33,34]. Here, it could be demonstrated that LTB4 also affects cell surface density of LFA-1 on human mast cells of the HMC-1 cell line.…”
Section: Discussionmentioning
confidence: 65%
“…The monoclonal antibody CBRM1/5 does not cross-react with inactive CD11b. It has been consistently shown to react only with activated CD11b on neutrophils [14][15][16] and eosinophils [17]. All flow cytometry samples, both conventional and high sensitivity, included matched isotype controls to control for nonspecific staining.…”
Section: Flow Cytometrymentioning
confidence: 99%